DynamiCC: a framework for dynamic context composition in ubicomp - Lopes, João; Souza, Rodrigo; Geyer, Cláudio; Gadotti, Gizele; Costa, Cristiano; Barbosa, Jorge; Gusmão, Márcia; Yamin, Adenauer (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2012: Proceedings of the 18th Brazilian Symposium on Multimedia and the Web, 2012)
Ubiquitous computing (Ubicomp) environments are characterized by high distribution, heterogeneity and dynamism. In these environments, applications must be aware of their contexts and adapt to changes in them. A major research challenge in the area of Ubicomp is related to context awareness. Considering the characteristics of ubiquitous environments, this paper presents a framework for context awareness, called DynamiCC (Dynamic Context Composition), which includes elements to support context modeling, contextual data collection, environment actuation, composition and interpretation of contextual information. We consider that the main contributions of this work are the use of a hybrid approach for context modeling, and the proposal of an architecture that supports interpretation and composition of dynamic contexts. DynamiCC enables the construction of complex contexts at runtime. To assess the functionality of the proposed model, we developed usage scenarios.